THE IMPACT OF THE NASAL SPRAY FLUTIKAZON ON THE LOCAL IMMUNITY INDICES IN ALLERGIC RHINITIS PATIENTS - N.I. Kosyakova; A.A. Lyagina; L.A. Andreeva; E.B. Grazhdankin; A.A. Osnach (Union of pediatricians of Russia, 2006)
Medical library. medications - common over the counter medications the impact of a topical glucocorticoid flutikazon on the dynamics of the local immunity indices and microbiocenosis condition of the nasal mucosa was studied in the patients with the confirmed diagnosis of all the year round allergic rhinitis. In a year all patients demonstrated a sustained control of all the year round allergic rhinitis symptoms. A statistically significant increase of lysozyme, secretory and interferon γ concentration in the nasal and mouth mucous secretion as well as the decrease of tumor necrosis factor (TNF) α concentration and the frequency of yeast like fungi and gram negative bacteria growth were revealed. Thus, long term flutikazon therapy has brought about a sustained remission of all the year round allergic rhinitis clinical manifestations as well as a significant improvement of microbiocenosis indices of the upper respiratory mucous membranes and local immunity indices.Key words: allergic rhinitis, local immunity, mucous membranes microbiocenosis, topical glucocorticoids.